The Trend of Choosing Not to Have Children (Childfree) Perspective of the Concept of Interplay (Mubadalah) - Nurul Kartika Laili; Busriyanti; Lutfi Nur Cahyono (Jurnal Syntax Admiration, 2023)
The principle of mutual relations applies to husbands and wives, parents and children, individuals and families, employers and employees, government and citizens, and all individual citizens of the country. On the scale of family and small communities, someone who desires comfort must also provide comfort to others. The purpose of this research is to describe and analyze the phenomenon of childfree individuals in Indonesia and to describe and analyze the trend of choosing not to have children (childfree) from the perspective of the concept of mutual relations (mubadalah). This research uses a normative legal research method. The design in this research is a literature review (library research) using various literary sources as data sources in the study. The data collection technique in this research uses documentary techniques. The results of this research indicate that the childfree trend has five reasons, namely: a) personal reasons, in this case, the emotional and psychological aspects, b) psychological and medical reasons, which involve subconscious and physical aspects, c) economic reasons, relating to financial matters, d) philosophical reasons, related to principles, and e) environmental reasons, relating to the macrocosmic aspect.